High digestive hemorrhage in the elder patients.: fibroscopy diagnosis - Sojo, Enrique; Estapé, Gonzalo (Cirugía del Uruguay, 1978)
Out of a total of 1. 006 patients suffering from high digestive hemorrhage studied with fibroscopy those over 60 years of age were anaJ'yzed. This condition appears with greater frequency in males, with greater incidence of bleeding where there is predominance of chronic lesions ( 55 % ) over acute lesions ( 45 % ) . There is rarely any prior symptomatology in the older patient ( 45 . 7 % ) and coexistence of potencially bleeding lesions in the same or different organs. It is noteworthy that ingestion of gastro - duodenal mucosa agressors, most particularly acetilsalicilic acid and stress, pl'ay an important role